Sistem informasi Produksi Kopi Arabika Bajawa di Flores Nusa Tenggara Timur Berbasis Web - Maurianu Yulius Suru; Rini Agustina (JOURNAL OF INFORMATION TECHNOLOGY, INFORMATION SYSTEMS AND COMMUNICATIONS, 2023)
The development of the current information system has been combined with various aspects to assist humans in completing their work. One of the needs that needs to be developed is the production flow process from the processing of Bajawa Arabica Coffee. As the largest Arabica coffee producer, Flores has a special type of coffee and has a different aroma and taste than coffee in other regions in Indonesia. This Bajawa coffee is quite famous and much in demand from black coffee fans with a very strong taste. The management of Bajawa coffee production which is still not systemized makes coffee farmers feel disadvantaged by coffee processing companies. To avoid losses from both the farmer and the coffee processing company, a coffee production flow monitoring system was created in which coffee would be neatly recorded in and out, as well as the residue produced during processing, thereby eliminating suspicion from each party. By using the waterfall method this monitoring system is created and produces a fairly accurate and reliable system with good control functions at each stage.